2014
DOI: 10.15241/bes.4.5.467
|View full text |Cite
|
Sign up to set email alerts
|

Counseling Self-Efficacy, Quality of Services and Knowledge of Evidence-Based Practices in School Mental Health

Abstract: School counselors are a well-positioned resource to reach the significant number of children and adolescents with mental health problems. In this special school counseling issue of The Professional Counselor, some articles focus on systemic, top-down advocacy efforts as the point of intervention for addressing child and adolescent mental health. Other articles investigate improving child and adolescent mental health through a localized, groundlevel approach by developing school counselors' competency areas and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 53 publications
1
28
0
Order By: Relevance
“…For example, counselor educators who held positive attitudes toward EBPs saw few barriers in incorporating them when training counselors (Patel, Hagedorn, & Bai, 2013). Schiele, Weist, Youngstrom, Stephan, and Lever (2014) found that school mental health professionals, after receiving training on the use of EBPs, had increased levels of self-efficacy and greater likelihood to use EBPs when treating students for depression. Aarons et al (2010) found that older mental health providers were more open to adopting EBPs, if required, suggesting that formalized EBP policies and practices be in place for younger service providers.…”
Section: School Counselors' Use Of Data-driven and Ebpsmentioning
confidence: 99%
“…For example, counselor educators who held positive attitudes toward EBPs saw few barriers in incorporating them when training counselors (Patel, Hagedorn, & Bai, 2013). Schiele, Weist, Youngstrom, Stephan, and Lever (2014) found that school mental health professionals, after receiving training on the use of EBPs, had increased levels of self-efficacy and greater likelihood to use EBPs when treating students for depression. Aarons et al (2010) found that older mental health providers were more open to adopting EBPs, if required, suggesting that formalized EBP policies and practices be in place for younger service providers.…”
Section: School Counselors' Use Of Data-driven and Ebpsmentioning
confidence: 99%
“…Nineteen items required reverse scoring (Item 2,6,7,9,16,18,19,21,22,23,24,26,27,28,31,33,35,36,and 37). The instrument reported a moderate correlation with counseling performance (Larson et al, 1992) and quality of practice among school mental counselor (Schiele et al, 2015) but there was a no relationship correlation with counselors' personal counseling experience (Drew et al, 2017).…”
Section: Methodsmentioning
confidence: 92%
“…These results are consistent with research indicating that counselor self‐efficacy can be built through role plays and feedback (Daniels & Larson, ), such as those provided in effective MI workshops (Schwalbe et al, ). This finding is particularly important because counselor self‐efficacy is associated with both the use of EBPs (Schiele et al, ) and the use of specific counseling skills (Iarussi et al, ). Thus, increasing counselor self‐efficacy is an important outcome for trainings intended to promote addiction practitioners' adoption of EBPs in their counseling practice.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, counseling selfefficacy is an important factor in the likelihood of counselors using specific counseling skills (Iarussi, Tyler, Littlebear, & Hinkle, 2013). For example, research by Schiele, Weist, Youngstrom, Stephan, and Lever (2014) indicated that, posttraining, counselor self-efficacy was associated with quality of practice, knowledge of EBPs, and use of EBPs. Therefore, increasing counselor self-efficacy is an important component of trainings intended to promote practitioner implementation of MI with clients posttraining.…”
Section: Counselor Self-efficacymentioning
confidence: 99%